Investigations of milk-fat lamb production practices for western Kansas, Colby. - Menzies, C.S.; Banbury, Evans E.; Spaeth, C.W. (Kansas Agricultural Experiment Station, 2011)
A flock of approximately 450 commercial finewool ewes is maintained at the Colby Branch Experiment Station. Ewes are purchased in early spring in Southwest Texas as yearlings and replaced after producing six lamp crops. The current flock consists of ewes that produced first, second, and fourth lamb crops. Purebred Hampshire rams are used. All lambs are sold for slaughter.
Keywords: Lamb; Ration; Alfalfa; Silage; Yield grade